The Agroecology Transition: Different pathways to a single destination - Eight country experiences - CGIAR Initiative on Agroecology (2023)
Agroecology is a transdisciplinary, participatory, and action-oriented approach for co-designing options that enhance food system resilience, equity, and sustainability. Working in eight countries of the Global South, the CGIAR Initiative on Agroecology seeks effective ways to put this approach into practice. In each country, the Initiative concentrates on one or two distinct territories referred to as “agroecological living landscapes” (ALLs), where it engages with researchers, farmers and their associations or communities, private companies, international and national non-governmental organizations as well as local, regional, and national policymakers. With food system actors (FSAs) and partners in each country, the Initiative has identified various entry points for the agroecology transitions, which are tailored to specific ALL contexts through a vision-to-action process with food system actors. The ALLs differ markedly in terms of climate, farming systems, soils, and other conditions that rural communities face. In seeking suitable entry points, the Initiative has built on important experience that each country gained previously in applying some of the 13 agroecology principles.